HOTEL RESORT DI TELAGA SARANGAN - Dewi Saraswati; Ahmad Farkhan; Amin Sumadyo (Universitas Sebelas Maret Surakarta, 2016)
The design of Sarangan Lake resort done by the needs of tourist on its area, unfullfield of tourist needs on accommodation facilities, increasing number of uncare building towards negative impact to the environment, so the purpose from this design is to get a building design that could provide accommodation facilities to the tourist of Sarangan Lake, with the design that concern about environment. The design issue is how ecological architect can be applied into design of Sarangan Lake resort. Design method is using architectural design, started from initial idea, preliminary understanding of architecture about the planned object, research and problem formulation, literature study as substantial reference, data analysis and information, analysis of general and specific approach towards designed object and formulation of design concept, analysis of design concept approach which more specific about the to-be-designed object, and architectural design transformation and preliminary design as well. The result is a design concept of resort hotel facilities as lodging accommodations by applying the characteristic of the ecological architect to the building design.